PENGARUH KUALITAS PELAYANAN KERAGAMAN PRODUK DAN SUASANA TOKO DALAM MENENTUKAN LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO KOSMETIK SOMAYA SITUBONDO - Ramadhanti, Alifia Ayu; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of the study was to determine the effect of service quality, product diversity and shop atmosphere on consumer loyalty, with customer satisfaction as an intervening variable at Somaya Situbondo Cosmetic Shop. The sampling technique used in this study was a saturated sample. Data analysis and hypothesis testing in this study using the Structural Equation Model - Partial Least Square (PLS-SEM). The results showed that service quality has a positive and significant effect on customer satisfaction, product diversity has a positive and significant effect on customer satisfaction, shop atmosphere has a positive and significant effect on customer satisfaction, service quality has a positive but insignificant effect on customer loyalty, product diversity has a positive and significant effect on customer loyalty, Shop atmosphere has a positive and significant effect on customer loyalty, customer satisfaction has a positive but insignificant effect on customer loyalty, service quality has a positive but insignificant effect on customer loyalty through customer satisfaction, product diversity has a positive but insignificant effect on customer loyalty through customer satisfaction, shop atmosphere has a positive but insignificant effect on customer loyalty through customer satisfaction.